A Proposal for the Implementation of an English for Specific Purposes Specialization in a Master's Degree Program in Second Languages and Cultures with Emphasis in English as a Foreign Language - Saborío Pérez, Ileana (2009)
Costa Rica, as a developing country, has been seeking growth by attracting international investment. In the last few years, however, a myriad of international companies of multiple working disciplines have been installed in Costa Rica, and they need a labor force that is competent not only in general English, but also in the technical English required. Higher education institutions (public and private) are not training ESP3 teachers at all; i.e, ESP education is being taught by untrained ESP teachers. In response to the above limitation, the Universidad Nacional, in its program of MSLC4, is designing a branch of ESP.